SHAPE Score vs. ASA Grading: A Comparative observational Study for Preoperative Risk stratification for adults undergoing elective surgery - Priya, H.Padma; .G, UMA; Mu, Raajaram.; Gautham, Deepa (Journal of Neonatal Surgery, 2025)
Background: Effective preoperative risk stratification is critical for optimizing surgical outcomes. However, the American Society of Anesthesiologists (ASA) Physical Status Classification System widely used is limited by subjectivity and lack of organ-specific assessment. The Silverman-Holt Aggregate Preoperative Evaluation (SHAPE) score addresses these limitations through a multidimensional framework. Objectives: To compare the efficacy of ASA grading and SHAPE scoring systems in preoperative evaluation of adult patients, presenting for elective surgery across different age groups and genders. Patient’s fitness for surgery and predictability of peri operative complications if any were compared. Methods: This prospective observational study included 500 adult patients undergoing elective surgery under general or regional anesthesia at a tertiary institution from January to December 2019. Patients were divided equally into ASA and SHAPE assessment groups by random allocation using lottery chit method. Demographic data, perioperative complications, and ICU admissions were recorded. Associations between age and ASA/SHAPE scores were analyzed using the chi-square test. Results: Demographic characteristics were comparable across groups (p > 0.05). A significant association was observed between age and ASA grade (χ² = 70.54, p = 0.0001), age and SHAPE score (χ² = 27.82, p = 0.0001). While ASA grades increased with age, SHAPE scores demonstrated superior granularity, revealing subtle risk elevations particularly in older adults. Conclusion: Both ASA grading and SHAPE scores reflect increased peri operative risk with advancing age. SHAPE scoring offers more detailed stratification by incorporating organ-specific dysfunctions and physical examination findings. These results support the SHAPE system’s potential as a more precise tool for preoperative assessment, warranting further validation in diverse clinical settings.